A near comprehensive phylogenetic framework gives new insights toward a natural classification of the African genus Cyrtorchis (Angraecinae, Orchidaceae). Issue 4 (29th June 2021) - Azandi, Laura N.; Droissart, Vincent; Sonké, Bonaventure; Simo‐Droissart, Murielle; D'haijère, Tania; Farminhão, João N.M.; Verlynde, Simon; Kaymak, Esra; Stévart, Tariq
Abstract: The genus Cyrtorchis is renowned for its conspicuous white, long‐spurred flowers, but also for its challenging problems of species delimitation due to the great morphological resemblance of their flowers. Based on a preliminary visual inspection of 1752 specimens, 27 morphogroups were defined including 6 unpublished taxa. Then, we used a representative sampling of 171 dried and alcohol‐preserved specimens representing 20 morphogroups to perform linear morphometrics through multivariate analyses on 43 morphological characters in order to confirm morphogroups delineation and identify their discriminant characters. Moreover, the monophyly of the two sections and of 21 morphological entities was tested through molecular analyses in order to produce a natural classification of the genus. DNA sequences from 69 Cyrtorchis specimens belonging to 15 published taxa (seven from C . sect. Homocolleticon, eight from C . sect. Cyrtorchis ), six putative new Cyrtorchis taxa, as well as four taxa used as outgroups, were produced using one nuclear (nrITS‐1) and five plastid regions ( matK, rps16, trnC‐petN intergenic spacer, trnL‐trnF intergenic spacer, ycf1 ), and were analyzed using maximum likelihood and Bayesian approaches. We used this phylogenetic framework to infer the morphological character‐state evolution of six floral traits and assess their taxonomic value. Morphological analysis revealed two groups corresponding to the published sections. However, while molecular results recovered the monophyly of C . sect. Cyrtorchis, C . sect. Homocolleticon appears paraphyletic. Of the 21 morphologically defined taxa that were included in the molecular analyses, eight, namely C. aschersonii, C. henriquesiana, C. monteiroae, C. praetermissa, C. ringens, and three new taxa were proven monophyletic. The delimitation of the 19 remaining morphologically identified taxa was assessed using morphological approach only. The ancestral state reconstruction provided new insights into character‐state evolution in the genus by inferring the insertion point of the stipites at the rear third of the length of the viscidium as one of the main synapomorphic characters supporting the monophyly of the genus. Furthermore, viscidium structure, stipites shape, and the lateral lobes of the rostellum were found to be important to infer phylogenetic relationships within the genus.